FORMAL ORAL INDONESIAN REGISTER USED IN OPEN EXAMINATION A SYNTHATICAL-PRAGMATIC STUDY - Sartini, Ni Wayan; Artawa, Ketut; Budiarsa, Made; Dhanawaty, Ni Made (e-Journal of Linguistics; Vol. 6. Januari 2012 No. 1)
This study explored the formal oral Indonesian register ‘Bahasa Indonesia ragam lisan formal’ (hereinafter referred to as BIRLF) used in open examinations from syntactical-pragmatic perspective. In general, this study aims at analyzing the grammatical-pragmatic elements of the formal oral register used in open examinations; in particular, it aims at analyzing the forms of speech acts and the forms of politeness used in the open examinations held at the University of Airlangga ‘Universitas Airlangga’ (Unair) and the State University of Surabaya ‘Universitas Negeri Surabaya’ (Unesa). The theories used were the structural theory and the theory of pragmatics. The structural theory was used to analyze the grammatical structures of the sentences used in the dialogues taking place in the open examinations. The theory of pragmatics used in this study refers to the theory of politeness proposed by Lakoff (1972), Leech (1983), Brown and Levinson (1987), and the theory of speech act developed by Austin (1962) and Searle (1975). The data analysis showed that, based on the direction of extension in which the verb was the center, and the extending components, eleven types of imperative sentences were found. The extension took place to the left, to the right and to the left and to the right from the verb simultaneously. The extending components included words, phrases, clauses and combinations of phrases and clauses. The interrogative sentences used were both the close interrogative sentences and the open interrogative ones. The declarative sentences used were the complex coordinative and subordinative ones. Deletion, pronominalization,, and repetition characterized the two types of sentences. To identify politeness, the layers of the components constructing the sentences were analyzed. The imperative politeness was expressed grammatically and lexically. Grammatically, the grammatical politeness was shown by passivizing the verb, shifting moods, and changing sequences. Lexically, politeness was expressed by adding lexical items functioning to refine the directive force. The interrogative and declarative politeness was shown by hedging utterances using words functioning as politeness markers.
Keywords: imperative, interrogative, declarative, and politeness